National Priorites and European Challenges in the reform process of the Social Protection and Employment policies in Greece, 1980-2004 - Σακελλαρόπουλος, Θεόδωρος; Οικονόμου, Χαράλαμπος (Social Cohesion and Development, 2016)
The reforms of social protection and employment policies that took place in Greece over the past three decades were dictated mainly by domestic priorities and needs. Contrary to international tendencies, social protection reforms in Greece obeyed mainly to the need for expansion of the welfare state in new areas, in order to fill the structural and historical social deficits. Policies and initiatives of European inspiration were succesfull only in so far as they pointed towards a direction of further strengthening of the welfare state